Impact of the COVID‐19 pandemic on cytology practice: An international survey in the Asia‐Pacific region. Issue 12 (15th September 2020) - Wang, Yeh‐Han; Bychkov, Andrey; Chakrabarti, Indranil; Jain, Deepali; Liu, Zhiyan; He, Shurong; Hanum, Sitti Fatimah; Bakrin, Ikmal; Templo, Felipe; Nguyen, Truong; Kumarasinghe, Priyanthi; Jung, Chan Kwon; et al.
Abstract : Background: The purpose of the current study was to examine the impact of coronavirus disease 2019 (COVID‐19) on various aspects of cytology practice in the Asia‐Pacific region. Methods: An online questionnaire was distributed to cytopathology laboratories in 24 Asia‐Pacific countries to explore the impact of restrictive measures on access to health care, use of general and personal protective equipment (PPE), and changes in cytology workflow and workload from February to April 2020. Results: A total of 167 cytopathology laboratories from 24 countries responded to the survey; the majority reported that restrictive measures that limited the accessibility of health care services had been implemented in their cities and/or countries (80.8%) and their hospitals (83.8%). The respondents noted that COVID‐19 had an impact on the cytologic workflow as well as the workload. Approximately one‐half of the participants reported the implementation of new biosafety protocols (54.5%) as well as improvements in laboratory facilities (47.3%). Rearrangement or redeployment of the workforce was reported in 53.3% and 34.1% of laboratories, respectively. The majority of the respondents reported a significant reduction (>10%) in caseload associated with both gynecological (82.0%) and nongynecological specimens (78.4%). Most laboratories reported no significant change in the malignancy rates of both gynecological (67.7%) and nongynecological specimens (58.7%) compared with the same period in 2019. Conclusions: The results of the survey demonstrated that the COVID‐19 pandemic resulted in a significant reduction in the number of cytology specimens examined along with the need to implement new biosafety protocols. These findings underscore the need for the worldwide standardization of biosafety protocols and cytology practice. Abstract : The current international survey from 24 countries in the Asia‐Pacific region demonstrates that the coronavirus disease 2019 (COVID‐19) pandemic resulted in a significant reduction in the number of cytology specimens evaluated along with the need to implement new biosafety protocols. These findings underscore the need for the worldwide standardization of biosafety protocols and cytology practice.